Functional and microbiological effects of a microencapsulated probiotic consortium on the ruminal microbiota in vivo and in vitro systems - Johanna Marcela Urán Velásquez; Mauricio Agudelo Rendón; Mariana Zapata; Wilyer García Arboleda; Sara Echeverri; Juan Camilo Arroyave Manco; Koen Venema; Juan Vasquez (Animal Biotechnology)
Fistulated animals and rumen simulation systems are essential for evaluating the effects of ingredients like probiotics, proposed as sustainable alternatives to growth-promoting antibiotics in ruminant nutrition. This study assessed the impact of microencapsulated probiotics on the structure and functionality of an initial ruminal microbial community using in vivo (IVV) and in vitro (IVT) systems. The IVT system was inoculated with rumen fluid obtained from the cattle animal used as IVV system. Over time, both systems were analysed for short-chain fatty acid (SCFA) production, microbial composition and functionality using next-generation sequencing. Physicochemical parameters were consistent across both systems and the inoculum, with an increase in propionate concentration observed. Although the microbial composition of IVV and IVT systems was highly similar (Pearson correlation of 0.869), significant differences in B-diversity were noted (p value = 0.023). The systems also exhibited high similarity in enzymatic profiles (correlation: 0.971) and metabolic pathways (correlation: 0.938), despite differences in functional B-diversity. Both systems showed increased production of fibrolytic enzymes, enhancing feed efficiency. The use of microencapsulated probiotics induced both taxonomic and functional changes in the initial microbial community of the IVT and IVV systems, which can be linked to the zootechnical effects of using probiotics as additives in ruminal animal nutrition.